Antifungal Prenylated Diphenyl Ethers from Arthrinium arundinis, an Endophytic Fungus Isolated from the Leaves of Tobacco (Nicotiana tabacum L.) - Zhang, Peng (Molecules, 2018)
An endophytic fungus Arthrinium arundinis TE-3 was isolated and purified from the fresh leaves of cultivated tobacco (Nicotiana tabacum L.). Chemical investigation on this fungal strain afforded three new prenylated diphenyl ethers (1–3) as well as three known analogues (4–6). Structure elucidation of the isolated compounds was carried out by analysis of 1D and 2D nuclear magnetic resonance (NMR) and high-resolution electrospray ionization mass spectroscopy (HRESIMS) spectra, as well as by comparison of those data with literature data. The absolute configuration of the stereogenic center at C-8 in 1 was assigned by comparison of the experimental and calculated ECD spectra. Compounds 1 and 2 showed selective antifungal activity against Mucor hiemalis with minimum inhibitory concentration (MIC) values of 8 and 4 μg/mL, respectively. Compounds 5 and 6 exhibited inhibitory activity against Alteraria alternata with an MIC value of 8 μg/mL. In the cytotoxic assay, 2, 5, and 6 displayed moderate in vitro cytotoxicity against the human monocytic cell line (THP-1 cell line), with IC(50) values of 40.2, 28.3, and 25.9 μM, respectively. This study indicated that endophytic fungi possess great potential for exploring new bioactive secondary metabolites.